MAKNA TÄªRTHA SIDDHAKARYA DALAM UPACARA DEWA YAJNA - Suta, I Made; Wika, I Made (PANGKAJA: JURNAL AGAMA HINDU, 2020)
TÄ«rtha Siddhakarya is a gift from Ida Sang Hyang Widhi to give sanctity to the ceremony that is carried out so that success can be achieved (Siddhakarya). Dalem Sidakarya is also a manifestation of witness Pituhu as a central figure who can connect or communicate actual all components, so that his presence is expected to neutralize the elements that are lacking in the implementation of Yajna. While the philosophical meaning of TÄ«rtha Siddhakarya is inseparable from the philosophical meaning of upakÄra that is used to obtain TÄ«rtha Siddhakarya, such as sesayut siddhakarya and typat siddhakarya. Sesayut Siddhakarya is a place for stoning Ista Dewata which is a means to invoke waranugraha in the form of TÄ«rtha Siddhakarya which will be used as a penyiddhakarya so that the Dewa YajÃ±a ceremony can end successfully.Â